Combined effects of daylight transmitted through coloured glazing and indoor temperature on thermal responses and overall comfort. (15th October 2018) - Chinazzo, G.; Wienold, J.; Andersen, M.
Abstract: This study investigates the effect of daylight transmitted through three coloured glazing types (blue, orange and neutral) on thermal responses and overall comfort, at three temperature levels (19 °C, 22 °C and 26 °C). The goal is threefold: (i) understand whether the colour can affect a perception other than the visual (i.e., the thermal); (ii) study whether colour interacts with temperature influencing thermal responses; (iii) examine the combined effect of colour and temperature on overall comfort. A total of 75 participants took part in a controlled experiment. Thermal responses were estimated with questionnaires about subjective thermal estimation and physiological measurements (skin temperature, heart rate and skin conductance). Statistical analyses revealed that daylight transmitted through coloured glazing affected participants' thermal responses, mainly psychologically rather than physiologically, resulting in a colour-induced thermal estimation . With a blue glazing, people felt colder and less comfortable than with a neutral one. With an orange glazing, people felt warmer and more comfortable than with a blue one. Results were independent of temperature levels, but occurred mainly at temperatures perceived as comfortable (26 °C) or close-to-comfortable (22 °C). Overall comfort was also affected, both at the beginning of the colour exposure by only the glazing's colour, and at the end of the exposure by both colour and temperature. Given the significance of effects for the short exposure time and for temperature ranges that are realistic indoors, these findings should be taken into consideration in practice for both comfort and energy savings purposes, especially in transitional spaces. Highlights: Daylight transmitted through coloured glazing affects the thermal responses of people, in line with the hue-heat-hypothesis. The mainly psychological effects, rather than physiological, result in a colour-induced thermal estimation . Results are independent of temperature levels and are mainly observable at comfortable or close-to-comfortable temperatures. Overall comfort is affected by colour at the beginning of the exposure and by colour and temperature at the end of it. Findings are applicable in practice, especially in transitional spaces.